LOL-Trasianka: what Language do the Belarus Network Communities Use? (Proceedings of Southern Federal University. Philology, 2021)
Tamara A. Pivovarchik, Inna I. Minchuk (Grodno, Republic of Belarus)The article is devoted to LOL-trasianka – a network variety of mixed Belarus-Russian speech, which is actively used in Belarus Internet communities as a source of comic and a trigger for laughing communicative situations. It was found that laughter discourse in LOL-trasianka is characterized by deliberate distortion of the norms of both Russian and Belarus languages, hypertrophied interference, violation of ethical and etiquette rules of communication, demonstrative marginalization of the speech flow, general intention of irony and sarcasm. Sociolinguistic and communicative-discursive factors that determined the status of LOL-trasianka as the main code resource of Internet communities with an ironic-grotesque discourse of a socially critical orientation are a) stereotypes of marking the state Russian and Belarus languages and their variants; b) strengthening the symbolic function of the Belarus language; c) disdainful attitude towards mixed Belarus-Russian speech; d) expanding the scope of use of trasianka. It was found that in the communicative interaction of participants in the analyzed communities, LOL-trasianka performs a number of functions: creative (is a means of self-expression of participants), emotional expressive (allows the writer to convey a palette of emotions), integrative (unites members of the online community), identification (provides adequate perception and understanding each other’s intentions), interpretive (forms an alternative laughing reality), dissociative (expresses the protest of community members, dissatisfaction with the surrounding reality).Key words: Belarus language, Russian language, Internet communication, Internet language, network community, substandard, trasianka, LOL-trasianka, laughing discourse, linguistic functions.DOI 10.18522/1995-0640-2021-2-87-99